Testing Assumptions of the Categorization Approach to Studying Sports Participation and Alcohol Use. (December 2018) - Clarke, Paige; Dodge, Tonya; Marzell, Miesha; Turrisi, Rob; Williams, Kevin
The present study tested whether playing football or lacrosse in high school is associated with more problematic alcohol use during college compared with playing other sports in high school. A sample of undergraduate males ( n = 2, 940) in their freshmen year who had played sports in high school completed a web-based questionnaire. Results showed that males who played lacrosse or both football and lacrosse in high school engaged in heavier alcohol use in college than males who played football or other sports in high school. In addition, males who played football in high school engaged in heavier alcohol use in college than males who played other high school sports. Thus, not all high school sports place males at equal risk for heavy alcohol use in college.